A new genus and species of Laelapidae (Acari: Mesostigmata) from Iran - Kazemi, Shahrooz; Beaulieu, Frédéric (Zootaxa, 2016)
A new monotypic mite genus of the family Laelapidae, Persicolaelaps gen. nov., is described to accommodate a new species, P. hallidayi sp. nov., on the basis of adult female specimens collected from decaying wood, soil and litter in northern Iran, Golestan and Mazandaran provinces, respectively. The new genus can be distinguished from other members of the family by a combination of morphological attributes, some of which are unique or rarely observed in laelapids, such as (1) a series of small subrectangular sclerites flanking dorsally coxae I and gnathosomal base and adjoining podal plates anterolaterally, which are extending from and fused with sternal shield between coxae I and II; (2) an epigynal shield, so broad as to reach or even overlap acetabula III–IV, posteriorly axe-shaped; (3) metasternal setae absent; (4) a typical anal shield, though capturing pair of opisthogastric setae JV3; (5) gnathotectum triangular and acuminate; (6) the presence of six setae on trochanter IV; (7) genu IV with two ventral setae (occasional in Laelapidae); (8) internal malae with a series of thick, elongate filaments.